Outcomes after Contralateral Anatomic Surgical Resection in Multiple Lung Cancer - Fourdrain, Alex; Bagan, Patrick; Georges, Olivier; Lafitte, Sophie; De Dominicis, Florence; Meynier, Jonathan; Berna, Pascal (The Thoracic and Cardiovascular Surgeon, 2020)
Background Patients treated surgically for lung cancer may present synchronous or metachronous lung cancers. The aim of this study was to evaluate outcomes after a second contralateral anatomic surgical resection for lung cancer.Methods We performed a retrospective two-center study, based on a prospective indexed database. Included patients were treated surgically by bilateral anatomic surgical resection for a second primary lung cancer. We excluded nonanatomic resections, benign lesions, and ipsilateral second surgical resections.Results Between January 2011 and September 2018, 55 patients underwent contralateral anatomic surgical resections for lung cancer, mostly for metachronous cancers. The first surgical resection was a lobectomy in most cases (45 lobectomies: 81.8%, 9 segmentectomies: 16.4%, and 1 bilobectomy: 1.8%), and a video-assisted thoracic surgery (VATS) procedure was used in 23 cases (41.8%). The mean interval between the operations was 38 months, and lobectomy was less frequent for the second surgical resection (35 lobectomies: 63.6% and 20 segmentectomies: 36.4%), with VATS procedures performed in 41 cases (74.5%). Ninety-day mortality was 10.9% (n = 6), and 3-year survival was 77%. Risk factor analysis identified the number of resected segments during the second intervention or the total number of resected segments, extent of resection (lobectomy vs. segmentectomy), surgical approach (thoracotomy vs. VATS), tumor stage, and nodal involvement as potential prognostic factors for long-term survival.Conclusion A second contralateral anatomic surgical resection for multiple primary lung cancer is possible, with a higher early mortality rate, but acceptable long-term survival, and should be indicated for carefully selected patients.
Keywords: lung cancer; lobectomy; multiple primary; mortality; survival